The Patient Participation Culture Tool for healthcare workers (PaCT-HCW) on general hospital wards: A development and psychometric validation study. (September 2016) - Malfait, S.; Eeckloo, K.; Van Daele, J.; Van Hecke, A.
Abstract: Background: Patient participation is an important subject for modern healthcare. In order to improve patient participation on a ward, the ward's culture regarding patient participation should first be measured. In this study a measurement tool for patient participation culture from the healthcare worker's perspective, the Patient Participation Culture Tool for healthcare workers (PaCT-HCW), was developed and psychometrically evaluated. Objectives: The aim of this study was to develop and validate a tool that measures the healthcare worker-related factors of patient participation and information sharing and dialogue in patient participation from the healthcare worker's perspective in order to represent the patient participation culture on general and university hospital wards. Design: A four-phased validation study was conducted: (1) defining the construct of the PaCT-HCW, (2) development of the PaCT-HCW, (3) content validation, and (4) psychometric evaluation. Settings: The Belgian Federal Government invited all Flemish general and university hospitals by e-mail to distribute the PaCT-HCW in their organization. Fifteen general hospitals took part in the study. Participants: Units for surgery, general medicine, medical rehabilitation, geriatric and maternal care were included. Intensive care-units, emergency room-units, psychiatric units and units with no admitted patients (e.g. radiology) were excluded. The respondents had to be caregivers, with hands-on patient contact, who worked on the same ward for more than six months. Nursing students and other healthcare workers with short-time internship on the ward were excluded. The tool was completed by 1329 respondents on 163 wards. Methods: The PaCT-HCW was psychometrically evaluated by use of an exploratory factor analysis and calculation of the internal consistency. Results: A model containing eight components was developed through a literature review, individual interviews, and focus interviews. The developed model showed high sampling adequacy and the Bartlett's test of sphericity was significant. An exploratory factor analysis identified eight components, explaining 49.88% of the variances. The eight original included components were retained. The PaCT-HCW also showed high internal consistency. Conclusion: The PaCT-HCW offers an in-depth and differentiated perspective of the healthcare worker-related factors of patient participation and information sharing and dialogue in patient participation. The PaCT-HCW has been developed thoroughly, resulting in a strong, psychometric evaluated tool and is a valuable measure for both scientists and clinicians to measure these two aspects in general and university hospitals. By using the PaCT-HCW, the opportunity is created to develop specific actions to improve patient participation.